Strategy for Developing Small Micro and Medium Enterprises of Culinary in Baturaja City, OKU Regency - Vitergo, Robi; Sari, Fifian Permata; Efrianti, Rini; Manggi, Anggi Fatmayati (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This study aims to examine internal and external elements in the development of Culinary MSMEs in Baturaja City, OKU Regency, to define the Culinary MSMEs' development plan to improve economic growth in Baturaja City, OKU Regency. This study employed the survey method of research. A SWOT analysis was utilized to analyze the data in this investigation. The study's findings reveal various internal and external aspects. Internal factors include strength, consumer service, promotional media, raw material availability, and labor. Weaknesses include a lack of ability to innovate products, a scarcity of development money, difficulties obtaining raw materials, and technological limits in manufacturing. In the meanwhile, external forces present opportunities: the consumer. According to the findings of the study, the development strategies used to develop culinary MSMEs in Baturaja City, OKU Regency are the SO Strategy (difference and development of quality-oriented products and the development of marketing or promotional strategies), the WO Strategy (development of more varied product designs and the development of production processes with the revitalization of more modern machines and equipment), and ST Strategy (a highly competitive product development with a characteristic load local, Credit policy with cheaper interest and simpler process and improvement of the quality of physical infrastructure as well), WT Strategy (Development of promotion to the market with more sophisticated media and Increased role of external institutions, associations of large entrepreneurs in the development of MSME businesses)